Growth performance of selected advanced mutant rice lines under drought stress environment / Muhamad Adib Najmi Ja’afar ... [et al.]. - Ja’afar, Muhamad Adib Najmi; Hasan, Nor’Aishah; Mohamed Azzeme, Azzreena; Ahmad, Faiz; Hussein, Sobri; Harun, Abdul Rahim; Hasan, Affrida Abu; Abd Aziz Shamsudin, Noraziyah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Water scarcity caused millions of ringgit losses in a vast Malaysia from 2017 to 2021 in vast area of rice fields. The development of drought tolerant varieties is vital as most Malaysian rice varieties are drought-susceptible. Hence the aim of this project was to study the performance of advanced mutant rice lines (Oryza sativa L.). on phenotypic and genotypic coefficients of variation, broad sense heritability, genetic gain and correlations. The experiment was laid out in a randomized complete block design (RCBD) with three replications in the rice plot area of Sekinchan, Selangor during the 2020/2021 cropping season. All traits were drastically affected by the drought stress and significant reduction in their performance was also observed. Analysis of variance showed significant differences for all phenotypic and agronomic traits observed in a stressful environment. Genotypes differed significantly at p<0.05 for all the traits studied, which implies that the genotypes constitute a pool of germplasm with adequate genetic variability. Genotypic coefficients of variation were lower than the corresponding phenotypic coefficients in all the traits studied, indicating a considerable influence of the environment on the expression of the traits. Heritability showed two phenotypic and agronomic traits, namely, days to UFG and SF. These traits showed high heritability both under non-stress (control) (56.60-57.87) and stress (47.94-50.36%) environments. FLA had medium heritability under non-stress environment (15.98%) but low heritability under stress environment (7.37%). Several significant positive as well as negative correlations in a stressful environment were observed among the traits. Similar trends of correlation were also observed in non-stress environments. Grain yield exhibited a significantly positive correlation with the number of tillers per plant (r = 0.48*), filled grains per panicle (r =0.55*) and spikelet fertility (r= 0.69*). Therefore, the results suggest that these traits can be used for grain yield selection.